2021
DOI: 10.3171/2020.2.jns193226
|View full text |Cite
|
Sign up to set email alerts
|

Defining the optimal target for anterior thalamic deep brain stimulation in patients with drug-refractory epilepsy

Abstract: OBJECTIVEThe anterior thalamic nucleus (ATN) is a common target for deep brain stimulation (DBS) for the treatment of drug-refractory epilepsy. However, no atlas-based optimal DBS (active contacts) target within the ATN has been definitively identified. The object of this retrospective study was to analyze the relationship between the active contact location and seizure reduction to establish an atlas-based optimal target for ATN DBS. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 36 publications
0
21
1
Order By: Relevance
“…However, it may be explained, by the fact that the z coordinates of nonresponder contacts were substantially lower than ours. Guo et al [47] obtained a mean z coordinate in MNI space, of 6.01 mm for nonresponders and 9.50 for responders, while in our study, 40% of nonresponders presented a z coordinate superior to 9.50. This appears to demonstrate that both z inferior to 6 and much superior to 9.5 may not confer a benefit, which stands into agreement to our defined HELIA.…”
Section: Anteriorcontrasting
confidence: 60%
See 1 more Smart Citation
“…However, it may be explained, by the fact that the z coordinates of nonresponder contacts were substantially lower than ours. Guo et al [47] obtained a mean z coordinate in MNI space, of 6.01 mm for nonresponders and 9.50 for responders, while in our study, 40% of nonresponders presented a z coordinate superior to 9.50. This appears to demonstrate that both z inferior to 6 and much superior to 9.5 may not confer a benefit, which stands into agreement to our defined HELIA.…”
Section: Anteriorcontrasting
confidence: 60%
“…Koeppen et al [46] found better response rates with a center of stimulation 5 mm lateral to the wall of the third ventricle and 10 mm superior to the mid-commissural plane. Guo et al [47] found a positive relationship between the z coordinate of the final active contact and seizure reduction percentage, with a mean z coordinate in MNI space of approximately 9.5 mm and 6 mm in responders and nonresponders, respectively. They also found a negative relationship between distance of active contact to the center of the anterior half of ANT and seizure reduction percentage, suggesting this may be an optimal target for ANT-DBS.…”
Section: In Search Of the Ideal Target For Ant-dbsmentioning
confidence: 99%
“…In the case of CM stimulation for LGS, patients with >80 % seizure frequency reduction had electrodes within the anterolateral CM, whereas in those with <80 % reduction, electrodes tended more towards the superior, medial and posterior aspect of the CM [ 16 ]. For ANT stimulation, active contacts closer to the anterior half of the ANT were associated with improved seizure frequency reduction [ 26 ]. Here, we evaluated mean electrode distance from target and did not find a significant difference between responders and non-responders for either CM or ANT nuclei.…”
Section: Discussionmentioning
confidence: 99%
“…_ 1 ( _ _ ) / 2 y y y P C P LAS P RAS = + [10] and where S z =Cz/Pz is used to describe the scale transformation of the y-axis, and Cz and Pz are the differences between the z-axis coordinate values of PC and MC in the coordinate system and patient image, respectively, as defined below:…”
Section: Volume Registration For the Npc Roimentioning
confidence: 99%
“…Coordinate systems have been successfully applied in many studies (5,6), and anatomical landmarks have often been used to define coordinate systems. The results of most neuroimaging studies have been reported with Montreal Neurological Institute (MNI) coordinates (7)(8)(9)(10). In addition, a nonrigid image registration method, namely, large deformation diffeomorphic metric mapping, has been used to transform the MRI data of participants into the standard coordinate system (11,12).…”
Section: Introductionmentioning
confidence: 99%